Thoracic organ machine perfusion: A review of concepts with a focus on reconditioning therapies - Wagner, Mitchell J.; Hatami, Sanaz; Freed, Darren H. (Frontiers in Transplantation, 2023)
Thoracic organ transplantation, including lung, heart, and heart-lung transplants are highly regarded as gold standard treatments for patients suffering from heart failure or chronic end stage lung conditions. The relatively high prevalence of conditions necessitating thoracic organ transplants combined with the lack of available organs has resulted in many either dying or becoming too ill to receive a transplant while on the waiting list. There is a dire need to increase both the number of organs available and the utilization of such organs. Improved preservation techniques beyond static storage have shown great potential to lengthen the current period of viability of thoracic organs while outside the body, promising better utilization rates, increased donation distance, and improved matching of donors to recipients. Ex-situ organ perfusion (ESOP) can also make some novel therapeutic strategies viable, and the combination of the ESOP platform with such reconditioning therapies endeavors to better improve functional preservation of organs in addition to making more organs viable for transplantation. Given the abundance of clinical and pre-clinical studies surrounding reconditioning of thoracic organs in combination with ESOP, we summarize in this review important concepts and research regarding thoracic organ machine perfusion in combination with reconditioning therapies.